Design and Fabrication of an Innovative Rattan Splitting Machine for Efficient and Sustainable Production of High-Quality Rattan Material - A.L.S.S. Wijewickrama; Ishan Virantha; Lakshitha Kalhara; Deshan M Silva; Shanilka Abewardhana (Journal of Advanced Industrial Technology and Application, 2025)
This research was conducted to address the limitations of the traditional rattan splitting process, which had been time-consuming, labour-intensive, and heavily reliant on manual labour to produce thin strips for furniture and handicrafts. To improve productivity and alleviate physical strain on workers, a fully mechanical rattan splitting machine was developed and tested, purposely designed without modern technology that could be unfamiliar to the labour force. The machine was built with a durable blade system that precisely split rattan into thin, uniform strips, ensuring consistent, and high-quality results. Its compact and adaptable design included adjustable settings to accommodate different rattan sizes and thicknesses, powered by electricity for straightforward operation and maintenance. Research involved meticulous engineering design, material selection, prototype construction, and performance testing to measure efficiency, precision, and consistency in output quality. Key findings revealed significant reductions in manual labour requirements, increased production speed, and uniform quality in processed rattan strips. These results indicated that the machine had greatly enhanced productivity within the rattan industry, enabling larger-scale production with consistent quality. In conclusion, the mechanical rattan splitting machine provided a practical and efficient solution for the industry, transforming a labour-intensive process into a streamlined operation that increased productivity, lowered labour costs, and maintained product standards. This development represents a significant advancement for the rattan industry, offering a sustainable solution that meets the current capabilities of the workforce while supporting industry growth and modernization.